2015
DOI: 10.1001/jamaneurol.2015.1449
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Patterns and the Risk of Future Dementia in Early, Incident Parkinson Disease

Abstract: IMPORTANCE Alterations in cerebrospinal fluid (CSF) have been found in Parkinson disease (PD) and in PD dementia (PDD), but the prognostic importance of such changes is not well known. In vivo biomarkers for disease processes in PD are important for future development of disease-modifying therapies.OBJECTIVE To assess the diagnostic and prognostic value of a panel of CSF biomarkers in patients with early PD and related disorders. DESIGN, SETTING, AND PARTICIPANTS Regional population-based, prospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(136 citation statements)
references
References 41 publications
10
126
0
Order By: Relevance
“…Two cross-sectional studies reported an association between low CSF Aβ 42 levels and cognitive impairment in PD 90,91 . In addition, four longitudinal studies reported that reduced Aβ 42 predicted more rapid cognitive decline 9295 , confirming previous findings 9698 (TABLE 2). DeNoPa, a multimodal biomarker study in de novo PD 99 , found no link between PD progression and CSF markers, but the results could have been confounded by the low number of participants agreeing to serial CSF sampling, variations in CSF sample preparation, and the demographics of the cohort.…”
Section: Biomarkers Of Cognitive Decline In Pdsupporting
confidence: 87%
“…Two cross-sectional studies reported an association between low CSF Aβ 42 levels and cognitive impairment in PD 90,91 . In addition, four longitudinal studies reported that reduced Aβ 42 predicted more rapid cognitive decline 9295 , confirming previous findings 9698 (TABLE 2). DeNoPa, a multimodal biomarker study in de novo PD 99 , found no link between PD progression and CSF markers, but the results could have been confounded by the low number of participants agreeing to serial CSF sampling, variations in CSF sample preparation, and the demographics of the cohort.…”
Section: Biomarkers Of Cognitive Decline In Pdsupporting
confidence: 87%
“…Four studies were performed in North America (Liu et al 2015; Siderowf et al 2010; Stewart et al 2014; Terrelonge et al 2015) and five studies in Europe (Alves et al 2014; Backstrom et al 2015; Compta et al 2013; Hall et al 2015; Parnetti et al 2014). The studies involved 1218 subjects diagnosed with Parkinson's disease (PD).…”
Section: Resultsmentioning
confidence: 99%
“…While the effects on cognition were different for the COMT and DRD2 genotypes, none of the genotypes affected cerebrospinal fluid NFL concentration (which has been found predictive of PDD) 35. This suggests that the COMT and DRD2 genotypes did not affect cognition through gross effects on neurodegeneration, at least not as measured by injury of myelinated axons.…”
Section: Discussionmentioning
confidence: 80%